Prospects for the creation of a common market for transport services of the EAEU - E. V. Khokhlova; D. S. Grigoriev; V. A. Levchenko (Вестник Северо-Кавказского федерального университета)
The Eurasian Economic Union, in its development and formation, sets itself many goals and objectives: the formation of a common market for goods, capital, labor, including the creation of a common market for transport services. The purpose of the study is to analyze cargo and passenger turnover, to consider the prospects for creating a common market for transport services in the context of integration processes taking place in the Eurasian Economic Union. The study was conducted on the basis of statistical data of the Eurasian Economic Commission using general scientific research methods. The article considers the main provisions and objectives of a coordinated policy in the field of creating a single transport space; analyzes the statistics presented on this issue; describes the main stages of the implementation of the Coastal Transportation Program, the implementation of which is scheduled until 2025. The novelty of the work consists in analyzing problematic issues when creating a single transport space of the Union, highlighting the main priorities for achieving this goal.